Media literacy to identify fake news. Case study with fourth-year high school students from a school in Lima - Gómez Rojas, Diana Carolina (2023)
In a context where digital media increases the proliferation of information, this research addresses media literacy as a possible solution to fake news. This article analyzes the relationship that fourth-year high school students from a school in Lima have with the media they interact with, in order to evaluate the degree of development of their media literacy. To do this, the CRAAP test was applied, which allows us to know the criteria they take into account when distinguishing a fake news story from a true one based on levels of currency, relevance, authorship, accuracy, and purpose of the text. As a result, the students evaluated false and true information very similarly, leading to the conclusion that they do not possess an adequate level of media literacy. Additionally, some clues are given to interpret the problem.